STATUS GIZI BERDASAR INDEKS IMT/U DAN TB/U PADA ANAK BARU MASUK SEKOLAH DASAR DI PERKOTAAN DAN PEDESAAN - Dyah Umiyarni Purnamasari; Endo Dardjito; Kusnandar Kusnandar (Kesmas Indonesia, 2016)
The purpose of this study was to determine nutritional status according to IMT/U and TB/U index on elementary school children in urban and rural areas. This study used cross sectional design study, April to May 2014. The population is all elementary school students in Santo Joseph as urban and Larangan Elementary Schools as rural areas. Samples were taken by purposive sampling been 82 first-grade students at both the elementary school. Data analysis included univariate analysis with frequency distribution and bivariate analysis by T-test to determine differences in the nutritional status of children in urban and rural areas. The results show a higher wasted in rural areas (13.1%) than urban areas (2.3%), while the overweight higher in urban areas (27.3%) than rural (2.5%), there is a difference nutritional status according to IMT/U index in urban and rural elementary school students (p = 0.00 <0.05). Stunted in urban areas (4.5%) is not much different than children in rural areas (7.9%), bivariate analysis showed no differences nutritional status according to TB/U index in urban and rural (p = 0.355> 0.05). Suggested to carry out routine monitoring of nutritional status, especially in the new elementary school students as improve nutrition status of children.